Long-term survival with repeat resection for lung oligometastasis from pancreatic ductal adenocarcinoma: a case report - Ryota Matsuki; Masanori Sugiyama; Hidefumi Takei; Haruhiko Kondo; Masachika Fujiwara; Junji Shibahara; Junji Furuse (Surgical Case Reports)
Abstract Background Long-term survival after resection of metastases from pancreatic ductal adenocarcinoma is rare. Case presentation A 54-year-old man underwent pancreaticoduodenectomy (PD) for pancreatic ductal adenocarcinoma (PDAC) with UICC staging pT3N1M0 followed by adjuvant chemotherapy with gemcitabine (GEM). Three years after radical resection of the primary tumor, a tiny nodule was found in the lower lobe of the left lung. Despite treatment with GEM, it increased gradually, but no other metastases were found. Eighteen months after the first indication of the nodule, wedge resection was performed. Pathological examination of the nodule indicated a metastatic tumor from PDAC. Pulmonary metastasectomy was again performed for lung oligometastases at 77 and 101 months after PD. The patient has been asymptomatic without tumor recurrence for 4 years since the last pulmonary resection. Conclusions In PDAC, the treatment strategy for oligometastasis is controversial. However, a few cases of long-term survival after pulmonary metastasectomy for oligometastasis of PDAC have been reported. More such cases need to be studied to address this issue effectively.